The thinnest air - Kent, Minka (Seattle, Washington : Thomas & Mercer, 2018)
"Meredith Price is the luckiest woman alive. Her husband, Andrew, is a charming and successful financial broker. She has two lovely stepchildren and is living in affluence in a mountain resort town. After three years of marriage, Meredith's life has become predictable. Until the day she disappears. Her car has been discovered in a grocery store parking lot--purse and phone undisturbed on the passenger seat, keys in the ignition, no sign of struggle, and no evidence of foul play. It's as if she vanished into thin air. It's not like Meredith to simply abandon her loved ones. And no one in this town would have reason to harm her. When her desperate sister, Greer, arrives, she must face a disturbing question: What if no one really knows Meredith at all? For Greer, finding her sister isn't going to be easy...because where she's looking is going to get very, very dark."--Amazon.com
Keywords: Sisters -- Fiction; Missing persons -- Fiction; Thrillers (Fiction)